The impact of yoga on occupational stress and wellbeing: exploring practitioners’ experiences - Hagen, Ingunn; Hagen, Øivind (Frontiers in Public Health, 2024)
Background: Workplace stress is a serious problem globally. It represents a major threat to the UN's sustainability goal of good health and well-being (SDG 3). The purpose of this article is to explore how yoga may be a tool for increased wellbeing and stress management at work and in everyday life.To examine how yoga can facilitate employees' wellbeing and ability to cope with stress, we performed qualitative interviews with practitioners who did yoga regularly. We focused on how yoga was experienced by each of our interviewees and what practicing yoga meant to them. Our data material consists of thirteen semi-structured lifeworld interviews. The sample consisted of ten women and three men in the age range of 20-55 years old. The data was analyzed through a thematic analysis.The themes identified in the thematic analysis include: 1. Yoga as a tool for increased wellbeing, 2. Yoga for coping with stress and dealing with challenges, 3. The role of breathing, and 4. Contextual factors. While confirming other research findings, this article elaborates on aspects informants described as induced by yoga, like self-awareness, calmness, balance, mood-lifting, focus, presence, self-care, and mastery. These factors increased wellbeing, aspects which also facilitated the ability to cope with stress and experience less stress. Informants also emphasized that yogic breathing was a central factor in inducing wellbeing and in feeling less stressed. They also expressed that contextual factors, like time, teacher and location influenced how practicing yoga was experienced and made sense of.The study concludes with yoga being experienced as positive by the participants, by increasing their wellbeing, and their ability to cope with and feel less stressed, something which was facilitated by yogic breathing, and influenced by contextual factors.